Light-activation through indirect ceramic restorations: does the overexposure compensate for the attenuation in light intensity during resin cement polymerization? (Journal of Applied Oral Science, 2011)
OBJECTIVES: This study evaluated the effects of light exposure through simulated indirect ceramic restorations (SICR) on hardness (KHN) of dual-cured resin cements (RCs), immediately after light-activation and 24 h later. MATERIAL AND METHODS: Three dual-cured RCs were evaluated: Eco-Link (Ivoclar Vivadent), Rely X ARC (3M ESPE), and Panavia F (Kuraray Medical Inc.). The RCs were manipulated in accordance to the manufacturers' instructions and were placed into cylindrical acrylic matrixes (1-mm-thick and 4-mm diameter). The RC light-activation (Optilux 501; Demetron Kerr) was performed through a glass slide for 120 s (control group), or through 2-mm or 4-mm thick SICRs (IPS Empress II; Ivoclar Vivadent). The specimens were submitted to KHN analysis immediately and 24 h after light-activation. The data obtained at the 2 evaluation intervals were submitted to 2-way ANOVA repeated measures and post-hoc Tukey's test (pre-set alpha of 5%). RESULTS: Lower KHN was observed when light-activation was performed through SICRs for Eco-Link at all evaluation intervals and for Rely X ARC 24 h later. For Panavia F, no significant difference in KHN was observed between control and experimental groups, regardless of evaluation interval. Most groups exhibited higher KHN after 24 h than immediately after light-activation, with the exception of Rely X ARC light-activated through SICR, as no significant difference in KHN was found between evaluation intervals. CONCLUSIONS: Light overexposure did not compensate for light intensity attenuation due to the presence of SICR when Rely X and Eco-Link were used. Although hardness of such RCs increased over a 24-h interval, the RCs subjected to light overexposure did not reach the hardness values exhibited after direct light exposure.